Gamified working memory intervention enhances prefrontal neurocognitive plasticity during aging - Wang, Ping; Zhou, Zi-Xuan; Gao, Peng; Hou, Hai-Yan; Zhang, Jia-Xin; Li, Hui-Jie; Zuo, Xi-Nian (Psychology and aging, 2025)
Considering the critical role of working memory (WM) in age-related cognitive decline, WM interventions are proposed as an effective approach for promoting healthy aging. However, traditional WM interventions often yield limited results, possibly due to a lack of interest and challenge. In light of the recent prominent trend of gamification, this study developed a challenging gamified WM intervention aimed at improving WM and providing extensive cognitive benefits for older adults, along with entertainment. Seventy-six older adults were randomly assigned to either the WM intervention group or the active control group. All participants underwent twelve 1-hr training sessions spanning 6 weeks. For each participant, cognitive assessments were completed at pretest, posttest, and 6 months after the intervention while structural magnetic resonance imaging (MRI) and resting-state functional MRI scans were conducted before and after intervention. The results revealed significant improvements in WM, inhibitory control, visuospatial processing, and episodic memory among older adults following the intervention. The left frontal pole, located in the rostral prefrontal cortex (rPFC), exhibited increased cortical thickness accompanied by reduced functional homogeneity and weakened connectivity with the left inferior temporal gyrus. Further statistical learning analysis demonstrated a consistent relationship between the changes at the left frontal pole and improved WM performance, suggesting that the rPFC may support WM and play a protective role in brain aging. The findings highlight the broad benefits of the gamified WM intervention on neurocognitive plasticity in the rPFC of older adults, indicating its potential as a promising tool for mitigating neurocognitive decline during the aging process. (PsycInfo Database Record (c) 2025 APA, all rights reserved).